Pharmacokinetic Study and Optimal Formulation of New Anti-Parkinson Natural Compound Schisantherin A. (17th May 2015) - Sa, Fei; Guo, Bao Jian; Li, Sai; Zhang, Zai Jun; Chan, Hok Man; Zheng, Ying; Lee, Simon Ming Yuen
Abstract : Our recent studies showed that schisantherin A (StA) is a promising candidate for PD treatment, but the pharmacokinetic profile of StA is largely unknown. The effects of different formulations on the pharmacokinetics and bioavailability of StA were investigated by HPLC equipped with a vacuum degasser, a quaternary pump, a manual sampler, and an ultraviolet detector. The absolute bioavailability of StA in nanoemulsion formulation was significantly increased from 4.3% to 47.3%. To the best of our knowledge, this is the first report of absolute bioavailability for StA in rats and successful increase of bioavailability of StA by nanoemulsion formulation. The pharmacokinetic profiles of StA could be significantly improved by a safe nanoemulsion formulation. This study provides a successful example of advanced delivery system for improving the bioavailability of potential central nervous system (CNS) drug candidate with poor solubility. This novel approach could be an effective alternative solution to overcome the shortcomings of conventional poor drug delivery of CNS drugs. The results of present study not only indicate that StA has potential to be developed as a promising oral therapeutic agent for the management of PD but also shed light on novel way to improve bioavailability of PD drugs.